The significance of psychosocial well-being for trauma healing as seen in Randa Abdel's where the streets had a name - Lisa Aulia (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/ yna, c.1